Forest fragmentation in the Brazilian Amazon: evidence from land reform settlements along the Transamazon Highway and in Southern Pará - Wang, Chuyuan (Kansas State University, 2012)
The democratization of Brazil in 1985 brought hope and impetus for agrarian reform, especially after the proposal of a series of new settlement projects by many Presidents to expropriate and redistribute lands to the Brazil’s landless. The landless poor, however, took this new state-sanctioned program into their own hands and started occupying lands to build land reform settlements. Social Movement Organizations (SMOs) that were established and working illegally gradually emerged and invaded large private landholdings near urban areas with a specific political agenda, while far rural landless people targeted unclaimed open public forest for land occupation to build spontaneous land reform settlements. Both types of land occupation actions constituted the Direct Action Land Reform (DALR). Recent literature has outlined the socio-economic circumstance that affected DALR, DALR settlement formation process and its implication to deforestation; however, no research considers forest fragmentation in these land reform settlements and its relationship with demographic factors. In order to fill this gap in the literature, this thesis first compared the temporal and spatial dynamics of deforestation fragment patterns in spontaneous DALR settlements around the municipality of Uruará along the Transamazon Highway, and in SMO-led DALR settlements in Southern Pará region using satellite imagery from 1986 to 2010 and three landscape metrics (patch mean area, area-weighted mean shape index and patch cohesion index). Metrics results were then respectively analyzed with selected field survey data to discover the impacts of demographic factors on forest fragmentation in DALR settlements. Results showed that SMO-led DALR settlements in Southern Pará primarily exhibited larger, more irregularly shaped and more physically connected deforestation fragments than spontaneous DALR settlements in the Uruará region over the whole study period. Demographic factors that influenced forest fragmentation in DALR settlements included the number of people and children per household, family lot size, percentage of families receiving credit and the distance between the family lot and the nearest city. At last, constructive policy recommendations were provided based on research findings.
Keywords: Brazilian Amazon; Forest fragmentation; DALR settlement; landscape metrics; household features; Geography (0366)